Similar gene expression patterns characterize aging and oxidative stress in Drosophila melanogaster. - Landis, G.N.; Abdueva, D.; Skvortsov, D.; Yang, J.; Rabin, B.E.; Carrick, J.; Tavare, S.; Tower, J. (Proceedings of the National Academy of Sciences of the United States of America, 2004)
Affymetrix GeneChips were used to measure RNA abundance for approximately 13,500 Drosophila genes in young, old, and 100% oxygen-stressed flies. Data were analyzed by using a recently developed background correction algorithm and a robust multichip model-based statistical analysis that dramatically increased the ability to identify changes in gene expression. Aging and oxidative stress responses shared the up-regulation of purine biosynthesis, heat shock protein, antioxidant, and innate immune response genes. Results were confirmed by using Northerns and transgenic reporters. Immune response gene promoters linked to GFP allowed longitudinal assay of gene expression during aging in individual flies. Immune reporter expression in young flies was partially predictive of remaining life span, suggesting their potential as biomonitors of aging.